ORGANISME PERUSAK KAYU PADA RUMAH RAKYAT DIYOGYAKARTA - Barly Barly; Nana Supriana; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1986)
Many  householders in  Yogyakarta  find  that  tney  need to know  something about  wood  destroying  organisms.   This may  be because  they  suspect  a problem  exists  in their house,  or  because  they plan  to buy  or build new house,  and wish  to avoid  serious  problems   during  use. However,   not  all damage  observed  should  cause concern,   as some  insects  attact only green  timber  and  their activity   cease  when  the  timber  dries-up. On the  other  hand.  some  insects  cause extensive  and con- tinuing  damage  and  can  be difficult  or expensive   to control.